The trade union movement in Nigeria - Ananaba, Wogu. (London : C. Hurst, 1969)
The book is organized around a narrative of key events and personalities in the Nigerian labor movement, from the formation of the Railway Workers Union in the 1930s until the general strike of 1964.
Includes bibliographical references and index.
rpm 21/03/2018
Loans
Keywords: Labor unions; Nigeria